1975
DOI: 10.1172/jci108216
|View full text |Cite
|
Sign up to set email alerts
|

Adherence of bacteria to heart valves in vitro.

Abstract: A B S T R A C T The abilities of 14 strains of aerobic gram-positive cocci and gram-negative bacilli to adhere in vitro to human or canine aortic valve leaflets were compared. 2-mm sections of excised valve leaflets were obtained by punch biopsy and were incubated under standardized conditions in suspensions of bacteria. Valve sections were subsequently waslhed and homiogeniized, and quantitative techniques were used to determine the proportions of bacteria from the initial suspensions that had adhered to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1
2

Year Published

1978
1978
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 199 publications
(94 citation statements)
references
References 18 publications
3
84
1
2
Order By: Relevance
“…Previous in vitro studies have shown that S. aureus is more adherent than enteric gram-negative bacilli to the native endocardial surface (4,5,34). However, these studies are largely accomplished in systems where the assays were performed either in the presence of serum or devoid of plasma factors altogether.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous in vitro studies have shown that S. aureus is more adherent than enteric gram-negative bacilli to the native endocardial surface (4,5,34). However, these studies are largely accomplished in systems where the assays were performed either in the presence of serum or devoid of plasma factors altogether.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, S. aureus accounts for one-quarter to one-third ofthe episodes ofbacteremia associated with intravascular devices (3). One intriguing aspect of the pathogenesis of S. aureus bacteremic infections in a human host is the unique ability of the organism to adhere to and colonize the endothe-Receivedfor publication 4 June 1990 and in revisedform 25 January 1991. lium (4) during transient bacteremia (5,6). In the case ofcatheter-related bacteremia, the prevailing view is that bacterial colonization starts at the skin-catheter junction, advances down the fibrin-coated external surface of the device (7) and ultimately seeds the bloodstream (2).…”
Section: Introductionmentioning
confidence: 99%
“…This difference is statistically significant (X2 = 4.78, 0.02 < P < 0.05). (32). These two studies suggest that bacterial adherence in vitro may correlate with the relative predilection of certain organisms to produce endocarditis in vivo and also with the relative frequency of the disease in man.…”
Section: Scanning Electronmicroscopymentioning
confidence: 94%
“…Adherence rates upon damaged aortic valve leaflets were measured from several species and it was found that Enterococcus spp. and viridans streptococci showed the highest rates of adherence than Escherichia coli (84). The ubiquitous presence of fibronectin on damaged tissue enables a surface binding protein, Fim A, to aid in colonization.…”
Section: Viridans Streptococci and Infective Endocarditismentioning
confidence: 99%